Fear : Trump in the White House - Woodward, Bob (New York Simon & Schuster, 2018)
With authoritative reporting honed through eight presidencies from Nixon to Obama, author Bob Woodward reveals in unprecedented detail the harrowing life inside President Donald Trump's White House and precisely how he makes decisions on major foreign and domestic policies. Woodward draws from hundreds of hours of interviews with firsthand sources, meeting notes, personal diaries, files and documents. The focus is on the explosive debates and the decision-making in the Oval Office, the Situation Room, Air Force One and the White House residence.
Keywords: Presidents; Presidents; Presidents -- Biography; POLITICAL SCIENCE / American Government / Executive Branch; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State; POLITICAL SCIENCE / Security (National & International).; Politics and government; Presidents; Presidents -- Biography; History